2004
DOI: 10.1097/01.ccm.0000142574.00425.e9
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity in hospitalized patients receiving human albumin: A meta-analysis of randomized, controlled trials*

Abstract: Albumin reduces morbidity in acutely ill hospitalized patients. Concomitant administration of albumin in the control group can obscure the effects of albumin on clinical outcome in randomized trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
2
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(75 citation statements)
references
References 92 publications
1
64
2
8
Order By: Relevance
“…Furthermore, the superiority of colloid as compared to crystalloid solutions for resuscitation in specific groups of critically ill patients also remains a hypothesized but contentious issue. [7][8][9][10][11][12][13][14] A very large, well conducted multicentre randomized controlled trial of 6,997 heterogeneous critically ill patients in need of volume resuscitation compared 4% albumin to normal saline and found no difference in 28-day mortality between the two groups. 15 However, there was a trend towards lower mortality in a severe sepsis subgroup receiving albumin [relative risk ratio of 0.87 and 95% confidence intervals (CI) from 0.74-1.02].…”
mentioning
confidence: 99%
“…Furthermore, the superiority of colloid as compared to crystalloid solutions for resuscitation in specific groups of critically ill patients also remains a hypothesized but contentious issue. [7][8][9][10][11][12][13][14] A very large, well conducted multicentre randomized controlled trial of 6,997 heterogeneous critically ill patients in need of volume resuscitation compared 4% albumin to normal saline and found no difference in 28-day mortality between the two groups. 15 However, there was a trend towards lower mortality in a severe sepsis subgroup receiving albumin [relative risk ratio of 0.87 and 95% confidence intervals (CI) from 0.74-1.02].…”
mentioning
confidence: 99%
“…There are three Cochrane analyses [10,76,113] and two systematic reviews [46,110] on the application of albumin as volume replacement during the perioperative phase, investigating the effect of albumin as compared to a crystalloid or any other colloid volume substitute. Regarding mortality neither benefit nor harm was shown when using human albumin.…”
Section: Human Albuminmentioning
confidence: 99%
“…For an assessment of using human albumin as substitute in hypovolemia or for hemodynamic stabilization of adult nonseptic intensive-care patients, the following references were incorporated in the evaluation: [14,19,24,25,28,36,56,78,81,82,93,95,104,105,109,110,112]. The meta-analyses of the Cochrane Collaboration [81,82] are referred to in the following.…”
Section: Human Albuminmentioning
confidence: 99%
“…Recent data have suggested that the type of resuscitation fluid used to treat hemorrhagic shock can affect the physiologic response , and that colloid versus crystalloid resuscitation in the acute trauma setting remains a controversial subject of debate. Despite the negative perception for resuscitation, recent studies showed that human albumin, as a broadly binding protein, has been characterized as a scavenger in addition to being an anti-apoptotic agent or antioxidant (Esposito et al, 1989;Emerson, 1989;Zoellner et al, 1996;Kentner et al, 2002;Osband et al, 2004b), and no increased mortality has been documented with albumin administration in the trauma population (Cochrane Injuries Group Albumin Reviewers, 1998;Vincent et al, 2004;Dubois et al, 2006).…”
Section: Introductionmentioning
confidence: 99%